Technology Entrepreneurship Project (ENT 600) : Reebok / Khairulnizam Mohd Afendy - Mohd Afendy, Khairulnizam (2021)
Nowadays people need to practice active lifestyle even though they are busy with their daily routine. Currently there are so many products out there than can keep us active without going to the gym. In this case study, it shows that treadmill can give many benefit to user to keep training on aerobic exercise for example running, walking or climbing at their own home. In this case study, I have chosen Reebok sport brand. Reebok has produce wide range of sport equipments which one of it is the exercise treadmill and I did a SWOT analysis to investigate its strengths, weaknesses, opportunity and threat. Some of the strengths are involving SubLite cushioning technology, Orthopedic running belt, using 4HP AC motor and console panel provided. However, there are some weaknesses such as not high price. Despite the weaknesses, there are opportunity that comes with this exercise treadmill are user can enjoy the entertainment while workout, the treadmill provides training data, can prevent the occurrence of injury and able to train indoor with high intensity training.